2009
DOI: 10.1051/0004-6361/200811570
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive study of large-scale structures in the GOODS-SOUTH field up to ${\mathsf z} \sim $ 2.5

Abstract: Aims. The aim of the present paper is to identify and study the properties and galactic content of groups and clusters in the GOODSSouth field up to z ∼ 2.5, and to analyse the physical properties of galaxies as a continuous function of environmental density up to high redshift. Methods. We used the deep (z 850 ∼ 26), multi-wavelength GOODS-MUSIC catalogue, which has a 15% of spectroscopic redshifts and accurate photometric redshifts for the remaining fraction. On these data, we applied a (2+1)D algorithm, pre… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
65
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 47 publications
(74 citation statements)
references
References 72 publications
8
65
0
1
Order By: Relevance
“…Marchesini et al 2009;Eminian et al 2008;Lamareille et al 2008), the CB09 models give masses that are on average lower than the BC03 ones. In particular, the recent study by Salimbeni et al (2009) on a sample that partially overlaps with the present one showed that the average mass difference in their highest redshift bin (which includes the range z ∼ 2.5−3.5, see their Fig. 4) is around ∼30%, with a slight dependence on mass.…”
Section: Spectral Energy Distribution Fittingsupporting
confidence: 52%
“…Marchesini et al 2009;Eminian et al 2008;Lamareille et al 2008), the CB09 models give masses that are on average lower than the BC03 ones. In particular, the recent study by Salimbeni et al (2009) on a sample that partially overlaps with the present one showed that the average mass difference in their highest redshift bin (which includes the range z ∼ 2.5−3.5, see their Fig. 4) is around ∼30%, with a slight dependence on mass.…”
Section: Spectral Energy Distribution Fittingsupporting
confidence: 52%
“…We overplot on Figure 5 the position of overdensities found in the GOODS-S field by Salimbeni et al (2009). These have been derived from the GOODS-MUSIC catalogue using a smoothed 3D density searching algorithm.…”
Section: Overdensities In the 3d-hst Deep Fieldsmentioning
confidence: 99%
“…In the COSMOS field (see Figure 6), Scoville et al (2007) applied an adaptive smoothing technique (similar to Salimbeni et al 2009) to find large scale structures at z < 1. While their results do not constrain the size of the structure and are less sensitive to very compact overdensities, we do find that their detections in the 3D-HST footprint correspond to high overdensities in our work.…”
Section: Overdensities In the 3d-hst Deep Fieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our SAM we considered as groups structures with masses in the range 10 13.5 < M < 10 14.3 M and as clusters structures with mass M > 10 14.3 M . We note that selecting structures according to their mass makes little difference with data: in fact, the masses of groups or small clusters with σ < 700 km s −1 selected by Pentericci et al are of the order of 0.5 to few times 10 14 M (see also Salimbeni et al 2009). The predictions for the two modes are shown as shaded regions (see the figure caption for more details), up to redshift z ∼ 1 for groups and z ∼ 0.7 for clusters.…”
Section: Environmental Dependence: Agn In Groups and Clustersmentioning
confidence: 83%